German Version of the Inventory of Motivations for Hospice Palliative Care Volunteerism: Are There Gender Differences?. (February 2018) - Stelzer, Eva-Maria; Lang, Frieder R.; Hörl, Melanie; Kamin, Stefan T.; Claxton-Oldfield, Stephen
The present study examined gender differences in motivations for volunteering for hospice using a German version of the Inventory of Motivations for Hospice Palliative Care Volunteerism (IMHPCV). The IMHPCV was translated into German and back-translated into English following the World Health Organization's guidelines for the translation and adaptation of instruments. In an online survey, 599 female and 127 male hospice volunteers from hospice organizations throughout Germany completed the translated version of the IMHPCV, the Scales of the Attitude Structure of Volunteers as well as questions pertaining to their volunteer experience. Based on an exploratory structural equation modeling approach, adequate model fit was found for the expected factor structure of the German version of the IMHPCV. The IMHPCV showed adequate internal consistency and construct validity. Both female and male hospice volunteers found altruistic motives and humanitarian concerns most influential in their decision to volunteer for hospice. Personal gain was least influential. Men rated self-promotion, civic responsibility, and leisure as more important than women. Analyses provided support for the use of the IMHPCV as a measurement tool to assess motivations to volunteer for hospice. Implications for recruitment and retention of hospice volunteers, in particular males, are given.